eLingua : Issue 1 : March 2014 / Academy of Language Studies - Mohd Amin, Noraziah; SyedMohri, Syarifah Norrasyidah; Tazijan, Farina Nozakiah; Razali, Wan Noorli; Nah, Er Ann; Ismail, Rushita (Academy of Language Studies, 2014)
1. “MESRA CERIA” Programme with children of Rumah Kanak-kanak Taman : A total of 35 staff members of The Academy of Language Studies, UiTM Pulau Pinang participated in a community programme called Program Mesra Ceria Bersama Kanak-kanak Rumah Kanak- kanak Taman Bakti on 22 June 2013. This event took place at a welfare home for the neglected and abused children as young as a newborn to as old as 12 years. 92 children were involved in this programme.